The Preservation of Abdi Dalem Code Choice among the Members of Samman Ritual in Beraji Village Sumenep Madura, East Java - Sapran, Aditya Rizky Wibisono; Khasanah, Ismatul; Auliya', Muhammad Zainul (Bina Nusantara University, 2024)
The research aimed to describe the influence of the samman tradition through the usage of the abdi dalem code choice, which was uttered by the ritual members, specifically in Beraji Village, in their daily conversations to preserve a language. The research applied a descriptive qualitative method that employed several works of literature, including (1) sociolinguistic, (2) language maintenance, and (3) code-switching and code-mixing, to explore the maintenance of the abdi dalem code choice within the daily discourse of ritual members in Beraji Village Sumenep, Madura. The data were purposive recorded samplings and transcriptions of inserted abdi dalem code choice within conversations among Madurese who were active as members of the samman ritual in Beraji Village. The data were collected through ethnographic observations and then used to conclude how individuals preserved the abdi dalem code choice in their daily discourse by utilizing the transcribed lyrics of the samman ritual as the main parameter. The results show that six abdi dalem words remain as parts of daily conversations among ritual members in Beraji Village, specifically when the discourse involves (1) a teacher and a student, (2) a mother and a child, or (3) elderly colleagues. The discussion elucidates the sociocultural relationship between abdi dalem words in the samman ritual and the honorifical-generational implementation of the abdi dalem code choice among ritual members in Beraji Village Sumenep, Madura.